2017
DOI: 10.1253/circj.cj-16-1054
|View full text |Cite
|
Sign up to set email alerts
|

Novel Scoring System for Distinction Between Paroxysmal and Non-Paroxysmal Atrial Fibrillation

Abstract: Background: Distinction of paroxysmal atrial fibrillation (PAF) from non-PAF is important in clinical practice, but this is often difficult at the time of first documented AF. Given that fibrillation cycle length (FCL) is longer in PAF than in non-PAF, the aim of this study was to compare various clinical parameters including FCL to establish a scoring system to distinguish PAF and non-PAF. Methods and Results:The subjects consisted of 382 consecutive patients with AF on digital ECG at the present institute be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…FCL shows dynamic changes according to the phase of AF. We have previously reported a study in which FCL was helpful for distinguishing between paroxysmal and persistent AF [10]. In that study, prolonged FCL (> 165 ms) at the time of the first documented episode of AF was found to be an independent predictor of paroxysmal AF.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…FCL shows dynamic changes according to the phase of AF. We have previously reported a study in which FCL was helpful for distinguishing between paroxysmal and persistent AF [10]. In that study, prolonged FCL (> 165 ms) at the time of the first documented episode of AF was found to be an independent predictor of paroxysmal AF.…”
Section: Discussionmentioning
confidence: 91%
“…The methods used to measure FCL have been described elsewhere [10,11]. In brief, the V1 lead recording was analyzed in patients found to have AF on a surface 12-lead ECG.…”
Section: Fft Analysis Of Fibrillation Wavementioning
confidence: 99%
“…It has been reported that in the early stage of AF, the autonomic nervous system tends to cause tachycardia, but afterwards, the HR decreases over time. 24 The larger HRR group in the present study might have included more patients with permanent AF in the relatively early stage.…”
Section: Discussionmentioning
confidence: 95%